Child health care demand in a developing country: unconditional estimates from the Philippines - Hallman, Kelly (International Food Policy Research Institute, 1999)
This study examines how quality, price, and access to curative health care influence use of modern public, modern private, and traditional providers among 3,000 children age 0-2 years in Cebu, Philippines. The analysis relies on a series of household, community, and health facility surveys conducted in 33 rural and urban communities during 1983-1986. The inclusion of data on potential health care users and available providers makes it possible to investigate the impact of the health care environment on demand. Furthermore, since the study is not limited to only those children whose mothers report them as currently ill, it avoids the possible biases caused by using a sample comprised of those who self-report morbidity. Distance to care is important for reducing demand, unlike user fees that show no significant effects on the use of modern public or private services. The availability of oral rehydration therapy and child vaccines, as well as the proportion of doctors to staff, are important for increasing the use of public care, while supplies of intravenous diarrhea treatments raise the demand for private services. Nonmodern practitioners were used more if they had recently attended an nongovernment- or government-sponsored health training session. Parental human capital and household income increase the utilization of private services. Children who are male and younger than 6 months of age are more likely to be taken to private and traditional providers, the two more expensive types of care.